“My mind is not like before”: Psychosocial rehabilitation of victims of torture in Athens - Womersley, Gail; Kloetzer, Laure; Van den Bergh, Rafael; Venables, Emilie; Severy, Nathalie; Gkionakis, Nikos; Popontopoulou, Christina; Kokkiniotis, Manolis; Zamatto, Federica (Torture Journal, 2018)
Introduction: The dual trauma of being a victim of torture as well as a refugee is related to a myriad of losses, human rights violations and other dimensions of suffering linked to torture experienced pre-migration, as well as different forms of violence experienced during and after migration. Method: To present three case studies to explore culturally-informed perspectives on trauma among victims of torture and track trajectories of psychosocial rehabilitation in relation to environmental factors. The case studies are part of a larger qualitative study of asylum seekers and refugees in a center for victims of torture in Athens, managed by Médecins Sans Frontières and Babel in collaboration with Greek Council for Refugees, which follows beneficiaries, their care providers and community representatives and leaders. Results: Key themes emerging include the substantial psychological impact of current material realities of migrant victims of torture as they adapt to their new environment and engage in rehabilitation. Delayed asylum trials, poor living conditions and unemployment have a substantial impact on posttraumatic symptoms that in turn influence psychosocial rehabilitation. Personal, social, and cultural resources emerged as having a mediating effect. Discussion: The results highlight the significant impact of the political, legal, and sociocultural environment on psychosocial rehabilitation. Practical implications for interventions are to ensure holistic, interdisciplinary, and culturally sensitive care which includes a focus on environmental factors affecting resilience; and with a dynamic focus on the totality of the individual over isolated pathologies.